Endogenous sulfur dioxide is a novel adipocyte-derived inflammatory inhibitor - Zhang, Heng (Sci Rep, 2016)
The present study was designed to determine whether sulfur dioxide (SO(2)) could be endogenously produced in adipocyte and served as a novel adipocyte-derived inflammatory inhibitor. SO(2) was detected in adipose tissue using high-performance liquid chromatography with fluorescence detection. SO(2) synthase aspartate aminotransferase (AAT1 and AAT2) mRNA and protein expressions in adipose tissues were measured. For in vitro study, 3T3-L1 adipocytes were cultured, infected with adenovirus carrying AAT1 gene or lentivirus carrying shRNA to AAT1, and then treated with tumor necrosis factor-α (TNF-α). We found that endogenous SO(2)/AAT pathway existed in adipose tissues including perivascular, perirenal, epididymal, subcutaneous and brown adipose tissue. AAT1 overexpression significantly increased SO(2) production and inhibited TNF-α-induced inflammatory factors, monocyte chemoattractant protein-1 (MCP-1) and interleukin-8 (IL-8) secretion from 3T3-L1 adipocytes. By contrast, AAT1 knockdown decreased SO(2) production and exacerbated TNF-α-stimulated MCP-1 and IL-8 secretion. Mechanistically, AAT1 overexpression attenuated TNF-α-induced IκBα phosphorylation and degradation, and nuclear factor-κB (NF-κB) p65 phosphorylation, while AAT1 knockdown aggravated TNF-α-activated NF-κB pathway, which was blocked by SO(2). NF-κB inhibitors, PDTC or Bay 11-7082, abolished excessive p65 phosphorylation and adipocyte inflammation induced by AAT1 knockdown. This is the first report to suggest that endogenous SO(2) is a novel adipocyte-derived inflammatory inhibitor.